Implementasi Algoritma Modified K-Nearest Neighbor untuk Klasifikasi Indeks Kualitas Udara Perkotaan di Berbagai Negara - Ni Made Ayu Pranasanthi Dewi; I Made Widiartha (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
One important component for the sustainability of living organisms is the availability of clean air. Air pollution has detrimental repercussions such as deteriorating air quality, which can have harmful impacts on the environment. As a result, modeling and monitoring air quality are essential steps in reducing air pollution, and the Air Quality Index allows for the review of this monitoring. This study's objective is to apply the Modified K-Nearest Neighbor method in classifying urban Air Quality Index data from various countries. The